CHRISTOLOGIES AMONG THE CHRISTIANS OF NDIA IN KIRINYAGA WEST SUB-COUNTY OF KENYA - Kagwima, Hezron Mwangi; Osamba, Josiah Otieno; Murage, Josia Kinyuga (Analisa: Journal of Social Science and Religion, 2018)
The study evaluated Christologies among the Christians of Ndia, Kirinyaga West sub-county, Kenya. The objectives of the study were: to explore ontological Christologies; to investigate popular soteriological Christologies; to establish social, political and economic functional Christologies among Ndia Christians and; to examine the question of Christodicy in Ndia Christianity. 232 Christians were randomly selected to participate in the study. Questionnaires were issued to the participants. A 95.45% response rate was realized. Data was analyzed using descriptive statistics. The data showed that ontological Christologies among the Ndia Christians ignored the humanity of Jesus and elevated him to the position of the traditional Gikuyu deity, Ngai, while soteriological Christologies were well balanced. Functional Christologies and the question of Christodicy were too spiritualized and Satan was given too prominent a position such that devil worship could result from glorification of Satan as a very powerful being who is able to oppose and cause Jesus to fail in his duties. The study recommends that churches in Ndia should teach sound doctrinal positions emphasizing on the humanity of Jesus, encourage people to appreciate the relationship between work and wealth and medicine and healing, avoid giving Satan a prominent position and to reinterpret the Gikuyu deity,Ngai, to take the place of God-the-Father as opposed to the place of God-the-Son for construction of a “wholesome” Gikuyu theology. The study will be useful to social workers, scholars, churches and government agencies working with the Ndia.